A MODEL FOR STATIC AND DYNAMIC PHENOMENA IN DEPOSITION PROCESSES - Hasan, M.; Opheusden, J.H.J. van (IndoMS, 2007)
We have developed a model for friction in a dry granular material,that allows multiple reversible transitions between stick and slipcontacts. The ultimate purpose of the model is to simulatedeposition processes. During these processes a pile structure isformed that is repeatedly destabilised by addition of new material.The present model does not yet include rotation. The model is testedfor a few simple systems. Finally we perform more extensive granulardynamics simulations using the model for 2D and 3D systems. In eachsystem, a steady flow of material is dropped onto a rough surface.DOI :Â http://dx.doi.org/10.22342/jims.13.2.83.173-189